Board characteristic and Indonesian Islamic bank’s credit risk - Fitri Anisa Nusa Putri; Slamet Haryono; Narong Hassanee (Journal of Islamic Accounting and Finance Research, 2024)
Purpose - This study aims to analyze factors that influencing credit risk  in Indonesian Islamic banks based on the board characteristic.Method - This study is a quantitative method using secondary data from nine Indonesian Islamic banks during 2018 to 2022. The sample of this study was taken by purposive sampling method and the data were analyzed using panel data regression analysis, including the classical assumption, F-test and T-Test.Result - This study povides evidence that sharia supervisor board size and women on board of directors are negative and significantly related to credit risk. However, the education level of board of directors and indepedent commissioners does not influence Indonesian Islamic Bank’s credit risk.Implication - These findings have implications for regulators and policy study to streghthen the internal governance mechanism to protect the Indonesian Islamic banks from financial failures and increseas the trust of stakeholder thorugh the effectiveness of implementation good corporate governance.Originality - This study represents a novel contribution to the literature on the determinants of Indonesian Islamic Bank’s credits risk as it conceptualized the relationship between board characteristic  and the credit risk. This study represents the few that adopt comprehensive modeling approach by proposing the role of board of directors’ gender diversity and education level and Islamic governance context represented by sharia supervisory board.